Q&A - Ask Doubts and Get Answers
Q

Simplify (m^2-n^2m)^2 + 2m^3n^2

Q : 4      Simplify. 

              (viii) (m^2 -n^2m)^2+2m^3n^2

Answers (1)
Views

We use identity
       (a-b)^{2} = a^{2} - 2ab + b^{2}
           In this a =  m^{2} and b = n^{2}m
                                         (m^{2}-n^{2}m)^{2} = (m^{2})^{2} - 2(m^{2})(n^{2}m) + (n^{2}m)^{2}
                                                                      =  m^{4} - 2m^{3}n^{2} + n^{4}m^{2}
Now,    m^{4} - 2m^{3}n^{2} + n^{4}m^{2}  + 2m^{3}n^{2}
            =  m^{4} + n^{4}m^{2}

Exams
Articles
Questions